A simple and versatile method for microencapsulation of anti-epileptic drugs for focal therapy of epilepsy. Issue 36 (28th September 2015) - Chen, Yu; Yue, Zhilian; Moulton, Simon E.; Hayes, Patricia; Cook, Mark J.; Wallace, Gordon G.
<x xml:space="preserve">Abstract</x> Nearly 30% of epilepsy cases cannot be adequately controlled with current medical treatments.